EXPERIMENTAL STUDY OF A CYCLONE SCRUBBER AIR CONDITIONING SYSTEM USING FACTORIAL DESIGN - Elias, R. B.; Pécora, A. A. B. (Revista de Engenharia Térmica, 2014)
This work reports the results obtained in the experimental evaluation of an American type cyclone which has been modified and adapted to perform environmental air conditioning by evaporative cooling. Equipment was fitted with nozzles atomizers, which perform the injection of liquid transversely to the gas stream. The tests were carried out following a full factorial design of experiments in order to obtain the influence of the atomizer holes diameter and of the liquid/air flow ratio on the cyclone performance. The diameter of the atomizer insert holes was in the range of 2.8 to 3.6 mm and the liquid/air flow ratio was from 0.65 to 0.76 L/m3. The saturation efficiency (Es) of the cyclone was analyzed through the Response Surface Methodology (RSM). Saturation efficiencies between 45.9 and 62.2 % were obtained. The use of statistical techniques allowed the proposition of empirical correlations to predict the behavior of the system regarding the studied operational range. The results show that the cyclone scrubber equipment is a viable alternative to air conditioning for human standards.